Analysis of the Localization of physical expansion in Germi city, using VIKOR - Fariba Esfandiari; Soghra Jedi Gheshlagh Ilkhchi; Elnaz Piroozi (تحقیقات کاربردی علوم جغرافیایی)
ncompatibility natural environment in the areas of urban development can create various hazards as well as to provide natural, natural bed is capable of  In relation to climatic factors and soil, slope, climate and restrictions on the physical development of cities, the (Shia, 1369: 68). That threaten the lives of a lot of financial damage, so that a reduction in development processes and precludes the formation of the development process are stable. As a result of the planned development is greater than ever The development of the city due to factors such orientation should be Along with minimum harm to the environment is physical development. One is a Germi city of Ardabil province in the northwest and north of the province of Ardabil between ˚39 '10 - ˚38 '50 to the north of the Equator and ˚47 '25  - ˚48 '12 east of the Greenwich meridian. The city has a total area of square kilometers which is equivalent to 9.6 percent of 1725/ 2is Ardabil. The city due to its geographical location and placed on the steep and mountainous zone has numerous limitations. Therefore, investigating and analyzing natural phenomena and human factors area and will ultimately provide control measures and logical approach and limits of this process is essential. Therefore, in this study, We try to be as natural and human phenomena and limitations arising from the possibility of them have been studied in relation to the development of the Germi city And ways to determine optimal physical development of the city.